Analysis Of Factors Influencing The Conversion Of Rubber Land Into Oil Palm Plantations In Tengah Padang Village, Central Bengkulu Regency - Anton Feriady; Maheran Mulyadi; Rita Feni; Jon Yawahar; Elni Muthmainah; Edy Marwan (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2025)
Purpose : To identify the factors influencing the conversion of rubber plantations into oil palm plantations in Tengah Padang Village, Talang Empat District, Central Bengkulu Regency. Methodology: The research employed a survey method with a sample of 30 rubber farmers who had converted their plantations into oil palm. Data were analyzed descriptively and through multiple linear regression analysis with independent variables including farmer’s age, experience, number of family members, education, and rubber farming income. Results: Simultaneously, all independent variables significantly affected the converted land area, with an F-value of 66.592 and a significance level of 0.000 (<0.05). Partially, only the variable of rubber farmers’ income had a significant effect on land conversion decisions. This indicates that economic factors are the main drivers influencing farmers’ decisions to convert rubber plantations into oil palm, as lower rubber income encourages them to seek more profitable alternatives, namely oil palm. Findings: These results are important as inputs for local governments in formulating sustainable policies for plantation land-use management and control. Novelty: The study provides direct empirical data from farmers, offering a real picture of the socio-economic dynamics influencing land-use change in Central Bengkulu Regency. Originality: This research was specifically conducted in Tengah Padang Village and used direct samples from farmers who converted rubber plantations into oil palm plantations.Conclusion: Simultaneously, the factors of age, experience, education, number of family members, and rubber farmers’ income significantly influence the extent of land conversion to oil palm. However, partially, only rubber farmers’ income has a significant effect. Article Type: Research Article.